2009
DOI: 10.1002/jcb.22170
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidins protect cardiomyocytes from ischemia and reperfusion injury via Akt‐NOS signaling

Abstract: Ischemia/reperfusion (I/R) injury in cardiomyocytes is related to excess reactive oxygen species (ROS) generation and can be modulated by nitric oxide (NO). We have previously shown that grape seed proanthocyanidin extract (GSPE), a naturally occurring antioxidant, decreased ROS and may potentially stimulate NO production. In this study, we investigated whether GSPE administration at reperfusion was associated with cardioprotection and enhanced NO production in a cardiomyocyte I/R model. GSPE attenuated I/R-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 48 publications
(59 reference statements)
2
29
0
Order By: Relevance
“…These findings further suggest that overproduction of ROS plays a critical role in the cardiomyocytes injury induced by ischemia/reperfusion or H/R. It has also been reported that administration of antioxidants or free radical scavengers should give potential benefits by alleviating ischemia/ reperfusion injury (Shao et al, 2009).…”
Section: Discussionsupporting
confidence: 52%
“…These findings further suggest that overproduction of ROS plays a critical role in the cardiomyocytes injury induced by ischemia/reperfusion or H/R. It has also been reported that administration of antioxidants or free radical scavengers should give potential benefits by alleviating ischemia/ reperfusion injury (Shao et al, 2009).…”
Section: Discussionsupporting
confidence: 52%
“…Study had shown that GSPE stimulated nitric oxide production in untreated cardiomyocytes in a dose-dependent manner. 14) However the molecular mechanisms of the cardioprotection of GSPE are not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies were conducted using GSPE to demonstrate its cardioprotective ability in animals and humans. [10][11][12][13][14] Our previous work had shown GSPE reduced reperfusioninduced arrhythmias in rabbits. 15) In isolated rat hearts GSPE had been proved to reduce the incidence of reperfusion-induced VF and VT. 11) However the mechanism of this protection against reperfusion-induced VT, VF by GSPE remained unclear.…”
mentioning
confidence: 96%
“…After the membranes were blocked in 5% fat-free milk in TBS-Tween 20, they were probed with antibodies against phosphorylated Akt (Thr308 and Ser473), phosphorylated heat shock protein 27 (HSP27) (Ser82), total Akt, tubulin, and/or total HSP-27. Signals were amplified and visualized with horseradish peroxidase-conjugated secondary antibody and enhanced chemiluminescence (30). Densitometry was performed using ImageJ software (version 1.38, NIH).…”
Section: Methodsmentioning
confidence: 99%
“…A chargedcoupled device camera was used to monitor contractions and membrane changes over time in the same field of cells (ϳ70 ϫ 90 m). Fluorescent images were acquired from a cooled Cool-SNAP-ES camera (Photometrics, Tuscon, AZ), and changes in fluorescent intensity over time were quantified with MetaMorph software (Molecular Devices, Downington, PA) (30).…”
Section: Methodsmentioning
confidence: 99%